Manual Hippocampal Subfield Segmentation Using High-Field MRI: Impact of Different Subfields in Hippocampal Volume Loss of Temporal Lobe Epilepsy Patients - Peixoto-Santos, Jose Eduardo; Carvalho, Luciana Estefani Drumond de; Kandratavicius, Ludmyla; Diniz, Paula Rejane Beserra; Scandiuzzi, Renata Caldo; Coras, Roland; Blümcke, Ingmar; Assirati, Joao Alberto; Carlotti, Carlos Gilberto; Matias, Caio Cesar Marconato Simoes; Salmon, Carlos Ernesto Garrido; Santos, Antonio Carlos dos; et al. (Frontiers in Neurology, 2018)
In patients with temporal lobe epilepsy (TLE), the presurgical magnetic resonance imaging (MRI) often reveals hippocampal atrophy, while neuropathological assessment may show differential patterns of neuronal cell loss across hippocampal subfields. However, currently used methods to assess hippocampal subfield volume on MRI have difficulties to correctly identify the anatomic subfield borders. Our aim was to co-register histological and MRI data to 1) define the volume of each hippocampal subfield on MRI, 2) to correlate neuronal density and volume of each subfield with gross hippocampal volume. The latter will help to better understand the contribution and impact of each individual subfield when hippocampal atrophy is reported by clinical examination. T2-weighted images from six formalin-fixed control hippocampi were obtained at 4.7T MRI to evaluate the volume of each subfield at the anatomical level of the hippocampal head, body, and tail. Formalin-fixed coronal sections at the level of the body of 14 control cases, as well as tissue samples from 25 TLE patients, were imaged with a similar MRI sequence at 3T. Anatomical subfield delineation at 4.7T MRI was informed by 10-µm-thin microscopy slides, collected at every millimeter from control cases, and stained for Luxol Fast Blue. An additional section was collected at the level of the body from controls and TLE groups and submitted to NeuN immunohistochemistry for the evaluation of neuronal cell density. Whole hippocampal volumetric assessment in control cases revealed that the dentate gyrus (DG)+CA4 region, CA1, and subiculum accounted for almost 90% of the hippocampal volume, with larger variations across the hippocampal head, body, and tail. Compared to control cases, all TLE patients had significantly lower subfield volumes for DG/CA4, CA3, CA2, CA1, and the subiculum. Neuronal cell densities were always decreased in CA4, CA3, CA2, and CA1. Total hippocampal volume correlated, however, most significantly with DG and CA1 volumes and neuronal density. For the first time, we identified also subfield specific pathology patterns in volumetric MRI scans. Our data reinforced the importance of CA1 to the hippocampal volume of TLE patients and the importance of manual segmentation of anatomical boundaries to assess subfield-specific pathology patterns.